Autonomic nervous system in euthymic patients with bipolar affective disorder - Latalova, Klara; Prasko, Jan; Diveky, Tomas; Grambal, Ales; Kamaradova, Dana; Velartova, Hana; Salinger, Jiri; Opavsky, Jaroslav (Neuro endocrinology letters, 2010)
BACKGROUND: Autonomic nervous system (ANS) dysfunction and reduced heart rate variability (HRV) have been reported in a wide variety of psychiatric disorders, but have not been well characterized in bipolar patients in remission. We recorded cardiac activity and assessed HRV in bipolar outpatients in remission. AIMS: Ascertain if ANS decrease with the age of the patient; ascertain relation between activity of ANS and level of dissociation, and other components (age of patients, and age of disorder, dosage of psychotropic medication) METHODS: Autonomic nervous system (ANS) has been evaluated during orthostatic change in three positions (1 - lie down 5 minutes, 2 - stand up 5 minutes, 3 - lie down 5 minutes). The functioning of the ANS has been measured by the diagnostic systems that are using the power spectral analysis which quantifies the heart rate variability (HRV) was assessed using time domain, frequency domain, and nonlinear analyses in 23 bipolar patients in remission. RESULTS: We found highly statistically significant negative correlations between level of dissociation measured by DES (Dissociative Experience Scale) and most of parameters of ANS. We found negative correlations between the age of the patient and activity of ANS, and negative correlations between activity of ANS and duration and onset of disorder. CONCLUSIONS: Autonomic dysregulation is associated with bipolar disorder in remission and has relation to level of dissociation and probably to age of patients and age of onset and duration of disorder.
Keywords: afekt; Humans; Outpatients; lidé středního věku; antidepresiva; Antidepressive Agents; Female; dospělí; Heart Rate; věkové faktory; výsledek terapie; lidé; Affect; bipolární porucha; indukce remise; Adult; antipsychotika; ženské pohlaví; Male; srdeční frekvence; Middle Aged; pacienti ambulantní; Bipolar Disorder; Treatment Outcome; Remission Induction; autonomní nervový systém; Antipsychotic Agents; Age Factors; Autonomic Nervous System; věk při počátku nemoci; mužské pohlaví; Age of Onset